Comparing Structural Constraints for Accelerated Branch and Bound Solver of Process Network Synthesis Problems - Heinc, Emília; Bánhelyi, Balázs (Acta Cybernetica, 2024)
The P-Graph methodology can be used to find the optimal solution for large processing system. This methodology solves the combinatorial part of the problem more efficiently than the traditional branch and bound method due to the utilized relationships inherent in the structure. However, reducing the number of possibilities developed in the constraint functions also plays a major role in this algorithm. In this publication, we present a new constraint function that also takes into account the minimum cost structure and compares it with earlier versions.